(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ Approaches that attribute inequalities in access and use of the Internet to structural economic factors and contemplate the reproduction of individual off-line characteristics in the digital environment are predominant in the specialized literature. Recently, however, the focus has been shifting to the differences in patterns of digital inclusion according to characteristics of particular communities or territories. Methodology/approach/design ”“ The empirical study investigates to what extent the territory matters to explain the variability of Internet use and the existence of ICT skills. Based on a sample survey conducted in 2016, the study analyses data collected on the city of São Paulo/Brazil. Findings ”“ The results indicate that, in addition to socioeconomic conditions, territorial aspects are important for understanding digital inequalities. Nonetheless, it suggests that the level of territorial disaggregation must be taken into consideration when measuring the use of the Internet and ICT skills. Practical implications ”“ The study highlights the need for deeper theoretical and methodological considerations of social, institutional and regulatory factors that affect the scenario of online inequalities, including place-based effects of urban policies.